(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2018)
This essay provides a detailed commentary on questions concerning the law of procedure in the royal letter of Antigonus Monophthalmus on the projected synoecism of Teos and Lebedos (Welles, RC 3; 306-302 BC). For the relevant lines (24-43) an updated edition of the Greek text together with a translation is presented. The essay begins with some general considerations about the legal terms enklēma, symbolaion and synallagma in the surviving inscriptions of Asia Minor. These reveal that the difference between enklēma on the one hand and symbolaion / synallagma on the other hand is not based on a semantic level but rather expresses different stages of procedural law. The main part of the article first deals with trials between citizens of the same state and then continues with trials between citizens of different states. Both parts focus on reconstructing the legal steps an individual had to take during litigation. Especially for the summoning of the defendant (prosklēsis), which is the subject of the last chapter, the royal letter provides useful insight in the procedural law of Greek city states and its necessary changes in specific situations